(untitled) (Orfeu, 2024)
Our objective is to interrogate certain sedimented conceptions about the Blues showing how these notions came to create semantic-hermeneutic “noises” that, at times, prevented a broader and more complex understanding of this agelong Afro-American musical genre. Based on analyzes and arguments considering the Blues as a dynamic and procedural manifestation, we sought to deepen a structural understanding inextricably related to socio-historical-cultural factors. In this way, some stereotypes and established essentialist truths were called into question: those that summarize the Blues as a form of folkloric-popular song that is essentially sorrowful and sad. These reductionisms, intentionally or not, ended up excluding analyzes of the more celebratory, happy, malicious, and dancing Blues – elements that go beyond the work-religious matrices with their loads of suffering and/or drama. From the reflective pentad structure, process, function, meaning and hermeneutics, we focus on the search for conceptualizations and theoretical-analytical reviews based on transdisciplinary dialogues between Ethnomusicology, Musicology, History, Anthropology and Sociology.